Proposal of Brazilian National Program for Quality Control in the small animal PET scanners - Rodrigo Modesto Gadelha Gontijo (Brazilian Journal of Radiation Sciences, 2022)
In Brazil, currently there are six preclinical molecular imaging centers and seven different small animal PET systems in use. However, there is still no national specific legislation for research laboratories focused on preclinical molecular images, unlike clinical nuclear medicine centers. A standardization of quality control protocols is needed to harmonize the use of small animal PET scanners in the research field. Thus, the aim of this work was to propose a National Program for Quality Control (NPQC) for the preclinical PET imaging systems in Brazil. This work was based on the quality control tests performed in Molecular Image Laboratory LIM/CDTN based on NEMA NU 4-2008 as described and presented in doctoral thesis of GONTIJO, 2019. The proposal of the NQCP was based on the CNEN NN 3.05 Publication (2013) and includes fundamental tests to be adopted, if possible, in laboratory practice to corroborate the experimental data. The Quality Control Program implemented in LIM/CDTN is an innovative and unprecedented proposal in the scope of preclinical molecular imaging services in Brazil. Therefore, the LIM/CDTN Program was carried out as a pilot to evidence the applicability and viability of the NQCP using small animal PET scanners. Summarizing, this work presents a viable set of Quality Control tests and their periodicities like a proposal for standardization to harmonize the use of this imaging technology in the field of research. Therefore, a National Quality Control Program (NQCP) applied to small animal PET scanners.